Common Fixed Point of Generalized Berinde Type Contraction and an Application (European Journal of Pure and Applied Mathematics, 2024)
In this paper, we introduce $λ_{(s,φ,ψ,L)}$-generalized Berinde type contraction and obtain some common fixed point results for such class of contractions the setting of triangular $α$-admissible mappings with respect to $η$ in the framework of $b$-metric spaces. Our results generalize and extend some theorems in the literature. An example is given to support our result.